The house of the green mask - Tobin, Paul, 1965- (Bandette, 2021)
"The greatest thief in all the lands, uncovers the greatest of all mysteries: a clue to the location of the legendary House of the Green Mask! But the sinister Voice has set his sights on the same treasure and sent a deadly assassin after the same secrets! Worse, he's stolen the one thing dearest to Bandette's heart. Now, she's after revenge! (And also chocolate.)"--